Has Everything Been Invented? On Software Development and the Future of Apps. - Malizia, Alessio; Olsen, Kai A. (Computer (00189162), 2011)
Because we're continually offered an abundance of new apps, we may fall into the trap of thinking that everything in software has been invented.